2022
DOI: 10.1021/acsomega.2c03023
|View full text |Cite
|
Sign up to set email alerts
|

Radiolabeled Trastuzumab Solid Lipid Nanoparticles for Breast Cancer Cell: in Vitro and in Vivo Studies

Abstract: Radiolabeled trastuzumab (TRZ) loaded solid lipid nanoparticles (SLNs) were prepared by high shear homogenization and sonication techniques. The apoptosis mechanism of TRZ-SLNs was studied only with the MCF-7 cell line, while the cytotoxicity and cell binding capacity were investigated using breast cancer cells (MCF-7 and MDA-MB-231) and the human keratinocyte cell line (HaCaT). The particle sizes of TRZ-SLNs were found to be below 100 nm, and they possessed a negative charge. The high radiolabeling efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
0
5
2
Order By: Relevance
“…Also, in cell incorporation studies in cancer cells using [ 99m Tc]­NaTcO 4 as a control group, it was observed that the uptake of [ 99m Tc]­NaTcO 4 was found to be approx. 60% in MCF-7 (breast cancer cell line) cells, 50% in MDA-MB-231 (triple negative breast cancer cell line) cells at 120 min . Although it was observed that [ 99m Tc]­NaTcO 4 also showed uptake in cancer cells, in our study, it was observed that the radiolabeled niosome formulation showed much higher uptake than the control group.…”
Section: Resultscontrasting
confidence: 61%
See 1 more Smart Citation
“…Also, in cell incorporation studies in cancer cells using [ 99m Tc]­NaTcO 4 as a control group, it was observed that the uptake of [ 99m Tc]­NaTcO 4 was found to be approx. 60% in MCF-7 (breast cancer cell line) cells, 50% in MDA-MB-231 (triple negative breast cancer cell line) cells at 120 min . Although it was observed that [ 99m Tc]­NaTcO 4 also showed uptake in cancer cells, in our study, it was observed that the radiolabeled niosome formulation showed much higher uptake than the control group.…”
Section: Resultscontrasting
confidence: 61%
“…60% in MCF-7 (breast cancer cell line) cells, 50% in MDA-MB-231 (triple negative breast cancer cell line) cells at 120 min. 49 Although it was observed that [ 99m Tc]NaTcO 4 also showed uptake in cancer cells, in our study, it was observed that the radiolabeled niosome formulation showed much higher uptake than the control group.…”
Section: Resultscontrasting
confidence: 61%
“…A steroidal saponin called polyphyllin D (PD) is derived from the Paris polyphylla . In certain malignancies, it induces apoptosis . Its applications are limited because it causes hemolysis .…”
Section: Therapeutic Interventions Involving Nanocarriers For Managem...mentioning
confidence: 99%
“…It binds to the HER2 protein and prevents epidermal growth factor from entering cancer cells, preventing cell division and destruction of the immune system. TRZ can prolong the progression-free survival time of HER2-positive metastatic BC patients and is radiolabeled with 99 mTc for disease diagnosis . Using high-shear homogenization and sonication techniques, researchers developed radiolabeled TRZ-loaded SLNs found to be less than 100 nm in size with a negatively charged zeta potential.…”
Section: Therapeutic Interventions Involving Nanocarriers For Managem...mentioning
confidence: 99%
See 1 more Smart Citation